2022
DOI: 10.3390/electronics11162627
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Federated Learning-Based Intrusion Detection System for 5G Smart Grids

Abstract: As the core component of smart grids, advanced metering infrastructure (AMI) provides the communication and control functions to implement critical services, which makes its security crucial to power companies and customers. An intrusion detection system (IDS) can be applied to monitor abnormal information and trigger an alarm to protect AMI security. However, existing intrusion detection models exhibit a low performance and are commonly trained on cloud servers, which pose a major threat to user privacy and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Among the machine learning methods (in terms of detecting network attacks), the support vector machine method has the worst performance in terms of accuracy index. The proposed method is compared with machine learning and deep learning findings of previous research [49]. In [49], federated hierarchical learning is used to detect attacks on smart grids.…”
Section: Evaluation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the machine learning methods (in terms of detecting network attacks), the support vector machine method has the worst performance in terms of accuracy index. The proposed method is compared with machine learning and deep learning findings of previous research [49]. In [49], federated hierarchical learning is used to detect attacks on smart grids.…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…The proposed method is compared with machine learning and deep learning findings of previous research [49]. In [49], federated hierarchical learning is used to detect attacks on smart grids. Table 4 compares the proposed method with SVM, LR, KNN, MultinomialNB, and deep learning methods, such as GRU+MLP, DNN-3, Transformer-IDM, and DNN-16.…”
Section: Evaluation Resultsmentioning
confidence: 99%
“…Te accuracy of the proposed model was 93.6%. For intrusion detection in 5G smart grids, Sun et al [40] designed a neural network that utilized a transformer and hierarchical federated learning. Te authors reported an accuracy of 99.48%.…”
Section: Federated Learning For Security Monitoring In 5gmentioning
confidence: 99%
“…The authors in [35] proposed a transformer-based intrusion detection model (Transformer-IDM) in which the transformer and feature exaction layers are leveraged to process categorical and numerical features in order to improve the detection performance. They also introduced a hierarchical federated learning intrusion detection system to collaboratively train Transformer-IDM to protect user privacy in the core networks.…”
Section: Related Workmentioning
confidence: 99%